Fluorinated nano-particles and preparation method of waterproof synthetic leather loaded with fluorinated nano-particles

By using fluorinated acid ester and amino silanes to perform nucleophilic addition reaction in the absence of catalyst, fluorinated nanoparticles were prepared and loaded on the surface of the ultra-fiber leather in situ, the high preparation cost of fluorinated silica nanoparticles was solved and The problem of improving hydrophobic performance has achieved efficient and environmentally friendly fluorinated nanoparticles distribution and hydrophobic effect of ultra-fiber leather.

CN119243470APending Publication Date: 2025-01-03QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364397.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the preparation cost of fluorinated silica nanoparticles is high, the reaction conditions are harsh, and no improvement in hydrophobic performance applied to ultra-fiber leather has been found.

Method used

The fluorinated nanoparticles are prepared by using fluorine-containing esters that can undergo amineene addition and amino-containing silanes without catalysts to prepare fluorinated nanoparticles and load them on the surface of the ultra-fiber leather in situ to form a waterproof synthetic leather. .

Benefits of technology

The uniform distribution and high hydrophobic effect of fluorinated nanoparticles are achieved, which reduces preparation costs, reduces waste emissions, and improves the hydrophobic performance of ultra-fiber leather.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243470A_ABST
    Figure CN119243470A_ABST
Patent Text Reader

Abstract

The invention relates to fluorinated nanoparticles and a preparation method of waterproof synthetic leather loaded by the fluorinated nanoparticles. According to the preparation method, tetraethyl orthosilicate and aminopropyltriethoxysilane are taken as raw materials, a SiO2 nano-particle precursor is prepared by using a # imgabs0 # method, chemical modification is performed by using fluorine-free silane, the fluorinated nano-particles are prepared, and the preparation method is relatively mild, simple and feasible. In the process of loading the nanoparticles with different fluorine contents on the microfiber leather, the reaction operation is simple and convenient, and the yield is high. In the whole reaction process, the solvent is recycled, the reaction yield is improved, and environmental pollution is reduced. The fluorinated nano-particles prepared by the method are loaded on the microfiber leather through in-situ growth on the fiber surface, the fluorinated nano-particles are uniformly distributed on the fiber surface, the surface hydrophobic angle can reach 150 degrees or above, the hydrophobic effect of microfibers is improved, and the method has very important significance on development of new synthetic leather materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing novel waterproof leather by synthesizing fluorinated silicon dioxide nanoparticles using a new method, and belongs to the field of new materials. Background Art

[0002] Nanomaterials hold significant scientific significance, serving as a bridge between macroscopic materials and atomic or molecular structures. They are now widely used in diverse fields, including industrial production, healthcare, aerospace, and environmental protection, integrating diverse disciplines. SiO2 nanoparticles, due to their variable pore size, excellent surface reactivity, large specific surface area, and excellent biocompatibility, have become one of the most important nanomaterials in recent years. Functionalized nanoparticles combine the unique properties inherent to their microstructure with new functionalities gained through functional modification, making them highly researchable. Surface modification of nanoparticles has three significant effects. First, it enhances nanoparticle stability and effectively prevents aggregation. Second, modified nanoparticles can achieve compatibility between multiple functions. For example, when hydrophilic groups are attached to metal nanoparticles, the metal particles become water-soluble without conflicting properties. A second example of functional compatibility is when modified inorganic nanofillers are incorporated into organic polymers. Modification can avoid heterogeneity and incompatibility between the two phases, thereby improving the mechanical properties of the composite. Third, modified nanoparticles can self-organize. For example: CN103917546B discloses a method for preparing stable bare colloidal gold nanoparticles. The nanoparticles can then be subjected to partial or complete surface modification. The method comprises using bulk gold as a source material to prepare colloidal gold nanoparticles in a liquid by adopting a top-down nanomanufacturing method. The surface modification of these nanoparticles is performed by adding one or more types of ligands (each containing a functional group that exhibits affinity for the surface of the gold nanoparticles to produce a conjugate). Due to the high efficiency and excellent stability of the nanoparticles prepared by this method, the gold nanoparticle conjugates produced can have a surface coverage of functional ligands that can be adjusted to any percentage value between 0 and 100%. CN107835696B discloses an aqueous synthesis method for preparing silica nanoparticles (SNPs) and core-shell SNPs with a narrow size distribution of 2 to 15 nm in size and size control less than 1 nm (i.e., at the monoatomic layer level). The hydrophobic surface of the silica nanoparticles themselves is functionalized with surface ligands such as polyethylene glycol (PEG) groups, achieving hydrophilic and hydrophobic modification of silica and enriching the types of silica nanoparticles.

[0003] Fluorinated SiO2 nanoparticles offer numerous advantages over traditional nanoparticles. They combine the characteristics of SiO2 nanoparticles, such as variable pore size, good surface reactivity, flexible structure, large specific surface area, and excellent biocompatibility, with the high surface activity of fluorine groups, as well as excellent weather resistance and water resistance. For example, CN115340648A discloses a method for preparing a fluoropolymer containing fluorinated silica nanoparticles and a method for preparing a fluororubber. This invention involves the preparation of fluorinated silica nanoparticles, solving the problem of dispersing nanofillers in a fluororubber matrix. While ensuring good material uniformity, it also improves the composite's impact resistance and other properties.

[0004] Currently known reports all involve the preparation of fluorinated silica using fluorinated silanes as the reaction raw material. However, fluorinated silanes are expensive, and the sol-gel method is used to introduce fluorinated segments into the surface of the silica during the reaction, which places high demands on the reaction conditions involved in the sol-gel method. Therefore, how to prepare fluorinated nanoparticles through multiple reaction processes, reduce preparation costs, and how to recycle them to reduce reaction losses and increase reaction yield have become technical problems that need to be solved urgently. At the same time, there are no reports on the use of fluorinated SiO2 nanoparticles in microfiber leather to improve the hydrophobic properties of microfiber leather. For this reason, the present invention is proposed. Summary of the Invention

[0005] In view of the above-mentioned state of the prior art, the inventors of the present invention conducted in-depth research in the field of fluorinated nanoparticles and microfiber leather and found that using a fluorinated ester capable of undergoing amine-ene addition and an amino-containing silane as raw materials, a nucleophilic addition reaction can occur in the absence of a catalyst and without the need for an external initiator to produce fluorinated nanoparticles. The synthesized fluorinated nanoparticles are in situ loaded on the fiber surface of microfiber leather to prepare waterproof leather. Not only can the fluorinated nanoparticles be evenly distributed on the fiber surface, but the surface hydrophobic angle can reach more than 150°, thereby improving the hydrophobic effect of the microfiber leather. The present invention is completed based on the above-mentioned discovery.

[0006] Therefore, an object of the present invention is to provide fluorinated nanoparticles and a preparation method and use thereof. A SiO2 nanoparticle precursor solution was prepared using a two-step method. To further improve the performance of the SiO2 nanoparticles, they were modified with fluorinated esters via a mild reaction process to produce fluorinated SiO2 nanoparticles. This "two-step" reaction allows for the reuse of solvents, reducing waste emissions, making it relatively environmentally friendly and enabling the production of nanomaterials with higher yields.

[0007] A second objective of the present invention is to provide waterproof synthetic leather loaded with fluorinated nanoparticles and a method for preparing the same. This method utilizes the multidimensional network structure of synthetic leather, such as microfiber leather, as a loading substrate, allowing in-situ loading of fluorinated nanoparticles in a solution to produce waterproof synthetic leather. Electron microscopic observation reveals that the fluorinated nanoparticles are uniformly loaded on the fiber surface, significantly enhancing the hydrophobicity of the synthetic leather.

[0008] The technical solution for achieving the above-mentioned invention object can be summarized as follows:

[0009] The preparation method of fluorinated nanoparticles comprises the following steps:

[0010] Using tetraethyl orthosilicate (TEOS), ethanol and ammonia as raw materials, The SiO2 nanoparticle precursor is prepared by the method; the SiO2 nanoparticle precursor is then reacted with a fluorinated ester and an aminosilane by Michael amine ene addition reaction to prepare fluorinated nanoparticles.

[0011] According to the present invention, preferably, use In the process of preparing SiO2 nanoparticle precursor by the method, the reaction is carried out in a solvent; further preferably, the solvent is ethanol, tetrahydrofuran or dichloromethane;

[0012] Preferably, The reaction temperature is 25-35°C;

[0013] Preferably, ultrasound is performed 1-6 times during the reaction, and the reaction time is 1-3 hours.

[0014] According to the present invention, preferably, the temperature of the Michael amine ene addition reaction is 30-70°C;

[0015] Preferably, the reaction time is 1-3h;

[0016] Preferably, ultrasonication is performed 1-3 times during the reaction.

[0017] According to the present invention, preferably, the volume ratio of tetraethyl orthosilicate to ethanol is (1-5): (50-100);

[0018] Preferably, the volume ratio of TEOS to aminosilane is (2-6):(0.1-4).

[0019] According to the present invention, preferably, the aminosilane is a silane coupling agent containing an amino group, and more preferably is at least one of γ-aminopropyltriethoxysilane (KH550) and γ-aminoethylaminopropyltrimethoxysilane (KH-792).

[0020] According to the present invention, preferably, the fluorine-containing ester is an acrylic fluorine-containing ester, and more preferably is at least one of trifluoroethyl methacrylate, hexafluoroethyl methacrylate, nonafluoroethyl methacrylate, dodecafluoroethyl methacrylate, trifluoroethyl acrylate, hexafluoroethyl acrylate, nonafluoroethyl acrylate, and dodecafluoroethyl acrylate.

[0021] According to the present invention, fluorinated nanoparticles prepared by the above method are also provided.

[0022] According to the present invention, preferably, the microscopic morphology of the fluorinated nanoparticles is a spherical core-shell structure, and the core and shell of the core-shell structure are made of different component materials.

[0023] According to the present invention, preferably, the particle size distribution of the fluorinated nanoparticles is concentrated between 600 and 2300 nm.

[0024] According to the present invention, there is also provided use of the above-mentioned fluorinated nanoparticles in the preparation of waterproof synthetic leather. Preferably, the synthetic leather is ultrafine fiber leather, i.e., microfiber leather.

[0025] According to the present invention, there is also provided a method for preparing waterproof synthetic leather loaded with fluorinated nanoparticles, comprising the following steps:

[0026] The microfiber leather is placed in a fluorinated nanoparticle solution to carry out an in-situ loading reaction, and after the reaction is completed, a waterproof synthetic leather loaded with fluorinated nanoparticles is obtained.

[0027] According to the present invention, preferably, the in-situ loading reaction temperature is 10-30°C.

[0028] According to the present invention, there is also provided waterproof synthetic leather loaded with fluorinated nanoparticles prepared by the above method;

[0029] Preferably, the surface hydrophobic angle of the waterproof synthetic leather is 151°-159°.

[0030] According to the present invention, preferably, in the waterproof synthetic leather loaded with fluorinated nanoparticles, the mass ratio of the microfiber cloth after loading with the fluorinated nanoparticles to the microfiber cloth before loading is 1.1-1.9:1.

[0031] The beneficial effects of the present invention are as follows:

[0032] 1. Compared to the traditional method of preparing fluorinated silica through a sol-gel reaction using expensive fluorinated silane, the preparation process of the fluorinated nanoparticles in this invention is more gentle, simple, and cost-effective. The prepared fluorinated nanoparticles have a novel structure and a controllable fluorine content, making them more suitable for applications.

[0033] 2. The preparation method of the fluorinated nanoparticles of the present invention is relatively mild. The product is prepared by a "two-step method" through the sol-gel method and amine-ene addition. The solvent can be reused during the process, which reduces waste emissions, is relatively environmentally friendly, and achieves a higher yield of nanomaterials.

[0034] 3. The fluorinated nanoparticles prepared by the present invention are loaded on the microfiber leather by in-situ growth on the fiber surface. The fluorinated nanoparticles are evenly distributed on the fiber surface, and the surface hydrophobic angle can reach more than 150°, thereby improving the hydrophobic effect of the microfiber leather.

[0035] 4. The present invention only requires one step of reaction to load fluorinated nanoparticles on microfiber leather, and the reaction operation is simple and the yield is high. The amount of fluorinated nanoparticles loaded into the microfiber leather can be adjusted by adjusting the amount of reactants, which is flexible and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Graph showing the particle size distribution of fluorinated SiO2 nanoparticles obtained in Examples 1 and 2 of the present invention.

[0037] Figure 2 This is the infrared spectrum of the fluorinated SiO2 nanoparticles obtained in Examples 1-5 of the present invention.

[0038] Figure 3 Transmission electron micrographs of SiO2 nanoparticles obtained in Example 1(a) and Example 2(b) of the present invention.

[0039] Figure 4 These are macroscopic photographs of the products in Example 1 (left) and Example 2 (right) of the present invention.

[0040] Figure 5 These are scanning electron microscope images of the microfiber leather before and after being loaded with fluorinated nanoparticles in Test Example 2 of the present invention; microfiber leather without being loaded with fluorinated nanoparticles (left), and microfiber leather loaded with trifluoro SiO2 nanoparticles (right).

[0041] Figure 6 This is a thermogravimetric analysis diagram of the microfiber leather before and after loading the fluorinated nanoparticles in Test Example 3 of the present invention.

[0042] Figure 7 This is a diagram showing the hydrophobic performance of microfiber leather loaded with different fluorine contents in Test Example 4 of the present invention. DETAILED DESCRIPTION

[0043] The present invention uses tetraethyl orthosilicate (TEOS) as raw material, and uses A SiO2 nanoparticle precursor solution is prepared using a method. To further improve the performance of the SiO2 nanoparticles, they are modified using a fluorinated ester compound via a mild reaction process to produce fluorinated SiO2 nanoparticles. These fluorinated silica particles are then in situ loaded onto the fiber surface of microfiber leather to produce waterproof leather. The preparation of the fluorinated modified nanoparticles and their application in microfiber leather are highlights of this invention.

[0044] The method for preparing fluorinated nanoparticles of the present invention comprises the following steps:

[0045] Using tetraethyl orthosilicate (TEOS), ethanol and ammonia as raw materials, The SiO2 nanoparticle precursor is prepared by the method; the SiO2 nanoparticle precursor is then reacted with a fluorinated ester and an aminosilane by Michael amine ene addition reaction to prepare fluorinated nanoparticles.

[0046] In one or more preferred embodiments, the use In the process of preparing SiO2 nanoparticle precursor by the method, the reaction is carried out in a solvent; preferably, the solvent is ethanol, tetrahydrofuran or dichloromethane.

[0047] In one or more preferred embodiments, the solvent used to prepare the precursor is anhydrous ethanol; preferably, the volume ratio of tetraethyl orthosilicate to anhydrous ethanol is (1-5): (50-100).

[0048] In one or more preferred embodiments, the catalyst used to prepare the precursor is ammonia water; preferably, the volume ratio of tetraethyl orthosilicate to ammonia water is (1-5):(5-10).

[0049] In one or more preferred embodiments, The reaction temperature for preparing the precursor is 25-35°C;

[0050] Preferably, ultrasound is performed 1-6 times during the reaction, and the reaction time is 1-3 hours.

[0051] In one or more preferred embodiments, the temperature of the Michael amine ene addition reaction is 30-70°C;

[0052] Preferably, the reaction time is 1-3h;

[0053] Preferably, ultrasonication is performed 1-3 times during the reaction.

[0054] In one or more preferred embodiments, the volume ratio of TEOS to aminosilane is (2-6):(0.1-4); preferably, the aminosilane is a silane coupling agent containing an amino group, such as γ-aminopropyltriethoxysilane (KH550), γ-aminoethylaminopropyltrimethoxysilane (KH-792), etc.

[0055] In one or more preferred embodiments, the fluorine-containing ester is an acrylic fluorine-containing ester, such as trifluoroethyl methacrylate, hexafluoroethyl methacrylate, nonafluoroethyl methacrylate, dodecafluoroethyl methacrylate, trifluoroethyl acrylate, hexafluoroethyl acrylate, nonafluoroethyl acrylate, dodecafluoroethyl acrylate, etc.

[0056] According to the present invention, in one or more preferred embodiments, the fluorinated nanoparticles are prepared as follows:

[0057] Tetraethyl orthosilicate (TEOS) is used as raw material and ammonia water is used as catalyst to prepare a precursor at a constant temperature of 25-35°C; then TEOS and aminosilane in different ratios are added, and the reaction time is 4-10 hours, during which ultrasonic waves are applied 1-6 times; finally, a fluorinated acid ester is added and the reaction is carried out in a water bath at 30-70°C, with magnetic stirring for 2 hours and ultrasonic waves applied twice; after the reaction is completed, the preparation of fluorinated nanoparticles is completed.

[0058] According to the present invention, the fluorinated nanoparticles prepared by the above method have a microscopic morphology of a spherical core-shell structure, wherein the core and the shell of the core-shell structure are made of different component materials.

[0059] In one or more preferred embodiments, the particle size distribution of the fluorinated nanoparticles is concentrated between 600 and 2300 nm.

[0060] According to the present invention, the use of the above-mentioned fluorinated nanoparticles in the preparation of waterproof synthetic leather, preferably, the synthetic leather is ultrafine fiber leather, i.e., microfiber leather.

[0061] According to the present invention, there is also provided a method for preparing waterproof synthetic leather loaded with fluorinated nanoparticles, comprising the following steps:

[0062] The microfiber leather is placed in a fluorinated nanoparticle solution to carry out an in-situ loading reaction, and after the reaction is completed, a waterproof synthetic leather loaded with fluorinated nanoparticles is obtained.

[0063] In one or more preferred embodiments, the in-situ loading reaction temperature is 10-30°C.

[0064] According to the present invention, a method for preparing microfiber leather loaded with fluorinated nanoparticles can include: weighing an appropriate amount of microfiber cloth, placing it in a suitable container, and performing an in-situ loading process. The multidimensional network structure of the microfiber cloth serves as a loading substrate for the preparation of fluorinated nanoparticles. Electron microscopic observation reveals that loading occurs on the surface of the fibers, significantly improving their hydrophobicity. Upon completion of the reaction, the microfiber cloth is loaded with fluorinated nanoparticles.

[0065] According to the present invention, there is also provided waterproof synthetic leather loaded with fluorinated nanoparticles prepared by the above method;

[0066] Preferably, the surface hydrophobic angle of the waterproof synthetic leather is 151°-159°.

[0067] In one or more preferred embodiments, in the waterproof synthetic leather loaded with fluorinated nanoparticles, the mass ratio of the microfiber cloth loaded with fluorinated nanoparticles to the microfiber cloth before loading is 1.1-1.9:1.

[0068] According to the present invention, a preferred embodiment of the preparation of waterproof synthetic leather loaded with fluorinated nanoparticles comprises the following steps:

[0069] Step 1: Preparation of fluorinated nanoparticles

[0070] 50-100 mL of anhydrous ethanol, 5-10 mL of aqueous ammonia, and 5-10 mL of deionized water are mixed and poured into a round-bottom flask; 1-5 mL of TEOS is also added to the round-bottom flask; a magnet is added to the flask; the flask is placed on a magnetic stirrer and stirred at 25-35°C for 1-3 hours; then 6 mL of TEOS and aminosilane in a ratio of (2-6):(0-4) are added, and stirring is continued for 2-6 hours; finally, 2-6 g of a fluorinated acrylic acid ester is added, and the mixture is magnetically stirred in a water bath at 30-70°C for 1-3 hours.

[0071] After the reaction is completed, a milky white liquid is obtained, which is the fluorinated nanoparticle solution.

[0072] Step 2: Microfiber leather loaded with fluorinated nanoparticles

[0073] Place the sheared microfiber leather into the round-bottom flask used to prepare the fluorinated nanoparticles, allowing the leather to participate in the entire preparation process. Once the reaction is complete, the microfiber leather is loaded with fluorinated nanoparticles.

[0074] Principle of the present invention:

[0075] The present invention first utilizes A SiO2 nanoparticle precursor solution was prepared using a Michael amine-ene addition reaction, followed by the preparation of fluorinated nanoparticles to explore their application in microfiber leather. The preparation of fluorinated nanoparticles is relatively mild, using a sol-gel method and amine-ene addition reaction in a two-step process. The solvent can be reused during the process, reducing waste emissions and being relatively environmentally friendly, achieving a higher yield of nanomaterials. The method is a physical and chemical method for synthesizing monodisperse silicon particles, which was proposed by Werner et al. It was first discovered. It generally refers to a method of generating nano-silica particles by adding TEOS to ethanol and ammonia water. Michael addition is very commonly used in organic chemistry. It uses carbon anions to perform nucleophilic addition on the carbon-carbon double bond of unsaturated carbonyl compounds. For reactions containing amine compounds in the reaction system, the amine compounds can act as both nucleophilic reagents and alkaline catalysts during the reaction process. Therefore, the reaction can be carried out simply and quickly without the action of a catalyst, and the reaction yield is high. In the present invention, for example: a silane coupling agent (KH550) is used to react with a variety of methacrylic acid fluorinated esters to generate a series of fluorinated silanes with different fluorine contents. The reaction process is relatively mild and the reaction yield is high.

[0076] The present invention prepares fluorinated nanoparticles by first reacting a fluorinated ester capable of amine-ene addition with an amino-containing silane in a nucleophilic addition reaction in the absence of a catalyst or an external initiator to produce the fluorinated nanoparticles. This two-step process allows for the reuse of solvents, reduces waste emissions, is environmentally friendly, and enables the production of nanomaterials with a higher yield.

[0077] The present invention uses a sol-gel method to prepare a precursor, then utilizes an amine-ene addition reaction to prepare fluorinated nanoparticles. The fluorinated nanoparticles are then loaded onto microfiber leather fibers via an in-situ reaction method. Fluorinated nanoparticles with varying fluorine contents can be prepared and loaded onto microfiber leather, achieving a surface hydrophobic angle exceeding 150° and achieving a good hydrophobic effect. This provides a good raw material foundation for the further production of high-performance synthetic leather.

[0078] Taking KH550 and trifluoroethyl methacrylate as an example, the reaction technology route is as follows:

[0079]

[0080] The present invention will be described in detail below through specific examples, but is not limited thereto.

[0081] The raw materials used in the examples are all conventional commercially available raw materials, and the equipment used is all conventional equipment. The microfiber leather used is microfiber cloth.

[0082] Example 1:

[0083] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask and stir on a magnetic stirrer at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours to obtain the precursor. Finally, add 1.862 g of trifluoroethyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is trifluoro-modified SiO2 nanoparticles.

[0084] Example 2

[0085] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours to obtain the precursor. Finally, add 5.879 g of heptadecafluorooctyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is the heptadecafluoro-modified SiO2 nanoparticles.

[0086] The particle size analysis, infrared spectrum and transmission electron microscopy of the product obtained in Example 1-2 are as follows: Figure 1-3 As shown by Figure 1 It can be seen that the three samples, the precursor, trifluoro-modified SiO2 nanoparticles, and heptadecafluoro-modified SiO2 nanoparticles, all have distinct peaks located at 1574nm, 1045nm, and 1285nm, respectively, indicating that all samples contain only one primary particle size. The distribution of nanoparticles in the precursor sample is primarily concentrated between 900 and 2300nm; the distribution of trifluoro-modified SiO2 nanoparticles is primarily concentrated between 600 and 1750nm; and the distribution of heptadecafluoro-modified SiO2 nanoparticles is primarily concentrated between 800 and 2000nm. The particle size distribution widths of all three samples are relatively narrow, indicating that the prepared nanoparticles are relatively uniform in relative size.

[0087] Depend on Figure 2 It can be seen that the amino group in the precursor has not changed. However, after loading the fluorinated nanoparticles, the -1 and 2936cm -1 The peak appears at 1695cm, indicating that the amino bond disappears and the -NH bond is generated. -1 ~1630cm -1There is no obvious peak in the range, which proves that the double bond (C=C) participates in the reaction. The standard sample precursor and the fluorine-modified SiO2 nanoparticle sample are both at 1100 cm -1 ~1000cm -1 There is an obvious peak in the interval, indicating that the product contains carboxyl group (C=O).

[0088] In the precursor, trifluorinated SiO2 nanoparticles and heptadecafluorinated SiO2 nanoparticles Figure 3 Figure a shows the formation of spherical SiO2 nanoparticles during the precursor preparation process, with a relatively uniform distribution. Figure b shows the morphology of the trifluoromethane-modified SiO2 nanoparticles, which exhibit a distinct spherical core-shell structure. Core-shell nanomaterials consist of two different components, the core and shell of which are typically selected based on the material's ultimate application, providing greater functionality. Figure c shows that the heptafluoromethane-modified SiO2 nanoparticles are smaller in diameter, more concentrated, and clustered.

[0089] In summary, the "two-step method" for preparing fluorinated nanoparticles was successful, and the structure of the obtained product was in line with expectations.

[0090] Example 3:

[0091] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 2.763 g of hexafluorobutyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is the hexafluoro-modified SiO2 nanoparticles.

[0092] Example 4:

[0093] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 3.669 g of nonafluoropentyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is the nonafluoro-modified SiO2 nanoparticles.

[0094] Example 5:

[0095] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 4.42 g of dodecafluoroheptyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is the dodecafluoro-modified SiO2 nanoparticles.

[0096] Example 6:

[0097] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 1.693 g of trifluoroethyl acrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is trifluoro-modified SiO2 nanoparticle-2.

[0098] Example 7:

[0099] Measure 80 mL of anhydrous ethanol, 9 mL of aqueous ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 2.597 g of hexafluorobutyl acrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is hexafluoro-modified SiO2 nanoparticle-2.

[0100] Example 8:

[0101] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 3.503 g of nonafluoropentyl acrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is nonafluoro-modified SiO2 nanoparticles-2.

[0102] Example 9:

[0103] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 4.249 g of dodecafluoroheptyl acrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is dodeca-modified SiO2 fluorine nanoparticles-2.

[0104] Example 10:

[0105] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 5.708 g of heptadecafluorooctyl acrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid is obtained, which is heptadecafluoro-modified SiO2 nanoparticles-2.

[0106] Example 11:

[0107] The process of loading fluorinated nanoparticles on microfiber leather is as follows:

[0108] The sheared microfiber leather was placed into the round-bottom flask used to prepare the fluorinated nanoparticles in Example 1-5, and the fluorinated nanoparticles were loaded throughout the entire process. After the reaction was completed, the microfiber leather was loaded with fluorinated nanoparticles.

[0109] Comparative Example 1:

[0110] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask. Place the mixture on a magnetic stirrer and stir at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 1.219 g of ethyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid, the ethyl ester nanoparticles, is obtained.

[0111] Comparative Example 2:

[0112] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask and stir on a magnetic stirrer at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 1.503 g of butyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid, the butyl methacrylate nanoparticles, is obtained.

[0113] Comparative Example 3:

[0114] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask and stir on a magnetic stirrer at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 1.779 g of amyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid, the amyl methacrylate nanoparticles, is obtained.

[0115] Comparative Example 4:

[0116] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask and stir on a magnetic stirrer at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 1.823 g of heptyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid, the heptyl methacrylate nanoparticles, is obtained.

[0117] Comparative Example 5:

[0118] Measure 80 mL of anhydrous ethanol, 9 mL of ammonia, and 9 mL of deionized water, mix, and pour into a round-bottom flask. Add 4 mL of TEOS in four portions to the flask. Add a magnet to the flask and stir on a magnetic stirrer at 30°C for 2 hours. Then, add 6 mL of TEOS and aminosilane in a 2:4 ratio and continue stirring for 4 hours. Finally, add 2.192 g of octyl methacrylate and stir magnetically in a 50°C water bath for 2 hours. After the reaction is complete, a milky white liquid, the octyl methacrylate nanoparticles, is obtained.

[0119] Comparative Example 6:

[0120] The process of preparing microfiber leather loaded ester nanoparticles is as follows:

[0121] The sheared microfiber leather was placed into the round-bottom flasks used to prepare the different ester nanoparticles in Comparative Examples 1-5. The reaction was completed, and the microfiber leather was loaded with different ester nanoparticles.

[0122] The microfiber cloth loaded with fluorine-free nanoparticles has a certain degree of hydrophobicity, with a contact angle between 125°-145°. Compared with the microfiber cloth loaded with fluorine-containing nanoparticles, it has not yet reached super hydrophobicity.

[0123] Test Example 1:

[0124] Elemental analysis of the product obtained in Example 11, loaded with fluorinated nanoparticles, revealed that the loaded microfiber leather contained fluorine, a fluorinated ester. When heptadecafluorooctyl methacrylate was used, the mass ratio of fluorine was 2.48%, as shown in Table 1.

[0125] Table 1 Analysis of the contents of four elements in heptadecaprolactam nanoparticles

[0126]

[0127] Test Example 2:

[0128] The microfiber leather material loaded with fluorinated nanoparticles obtained in Test Example 11, the dispersibility of the microfiber leather loaded with fluorinated nanoparticles, as shown in FIG. Figure 5 shown. Figure 5 These are scanning electron microscope images of the microfiber leather before and after loading with fluorinated nanoparticles. The left side shows the fibers before loading, which are smooth, full, and tightly entangled. After loading with 17-fluorine nanoparticles, the nanoparticles are deposited on the fibers, the roughness of the fibers increases, and the nanoparticles are uniform and have strong regularity. There are many smaller particles on the surface of the synthesized large particles. This structure is conducive to the formation of multiple roughness structures, which helps to form a super-hydrophobic surface. Its surface is uneven, which increases the roughness of the surface. The 17-fluorine-modified SiO2 nanoparticles present a complex micron- and nano-scale surface structure. Its micron-scale structure is manifested as a network of pores between microspheres with a primary roughness, while the nano-scale structure is manifested as a secondary roughness of the microspheres and tiny protrusions on their surfaces. This micro-nano double network structure forms a peak-valley surface, which is conducive to the adsorption of air, so that water droplets can only contact the top of the protrusion and cannot completely wet the solid surface.

[0129] Test Example 3:

[0130] The thermal decomposition temperature of the microfiber leather material loaded with fluorinated nanoparticles obtained in Test Example 11 is as follows: Figure 6The thermal decomposition process of the three membrane samples can be divided into three stages: In the first stage (t≤400°C), it is clearly observed that the thermal decomposition temperature gradually increases with increasing heating rate. All three samples experience slight weight loss before 400°C, which is caused by the evaporation of water, small molecule monomers, and solvents.

[0131] The second stage is 400-500°C. Within this temperature range, the sample degrades rapidly and its quality drops sharply. The blank sample is mainly made of fiber. During this stage, the carbon fiber undergoes a carbonization reaction, and some carbon atoms react with oxygen to produce carbon dioxide and carbon monoxide, while releasing heat. The mass loss rate of the filter membrane containing trifluoro-modified SiO2 nanoparticles and the filter membrane containing heptadecafluoro-modified SiO2 nanoparticles in this stage accounts for about 55% of the entire process, mainly due to the decomposition of silicon fluoride. The mass loss rate reaches its maximum value in this process, mainly because of the influence of high temperature, the precipitation of volatiles inside, the combustion reaction of volatiles with the external air, and the fast thermal decomposition reaction rate.

[0132] The heat loss in the third stage (t>500°C) is mainly due to the carbonization reaction, and the thermal decomposition rate is relatively slow. The filter membrane containing trifluorinated SiO2 nanoparticles has a larger mass loss than the filter membrane containing heptadecafluorinated SiO2 nanoparticles. This is because increasing the fluorine content will reduce the mass loss of the sample during thermal decomposition. Fluorides generally have high thermal stability. Therefore, if the sample contains fluoride and is thermally decomposed at high temperature, the presence of fluoride may prevent the decomposition of other compounds, thereby reducing the mass loss of the sample.

[0133] Test Example 4:

[0134] The hydrophobic properties of the microfiber leathers loaded with different fluorine contents in Example 11 were tested. Figure 7 As shown in the figure, it can be seen that the contact angle of the microfiber leather loaded with nanoparticles of different fluorine contents shows a significant upward trend with the increase of fluorine content (from 3F, 6F, 9F, 12F to 17F). From this, it can be concluded that the fluorine content has a great influence on the hydrophobic effect.

[0135] The content of the present invention is not limited to the embodiments listed. Any equivalent transformation of the technical solution of the present invention made by ordinary technicians in this field after reading the description of the present invention is covered by the claims of the present invention.

Claims

1. A method for preparing fluorinated nanoparticles, comprising the following steps: Using tetraethyl orthosilicate, ethanol and ammonia as raw materials, The method is used to prepare a SiO2 nanoparticle precursor; the SiO2 nanoparticle precursor is then reacted with a fluorinated ester and an aminosilane by Michael amine ene addition reaction to prepare fluorinated nanoparticles.

2. The method for preparing fluorinated nanoparticles according to claim 1, characterized in that: use In the process of preparing SiO2 nanoparticle precursor by the method, the reaction is carried out in a solvent; preferably, the solvent is ethanol, tetrahydrofuran or dichloromethane.

3. The method for preparing fluorinated nanoparticles according to claim 1, characterized in that: use In the process of preparing SiO2 nanoparticle precursor, The reaction temperature is 25-35°C; Preferably, ultrasound is performed 1-6 times during the reaction, and the reaction time is 1-3 hours.

4. The method for preparing fluorinated nanoparticles according to claim 1, characterized in that: The temperature of the Michael amine ene addition reaction is 30-70°C; Preferably, the reaction time is 1-3h; Preferably, ultrasound is performed 1-3 times during the reaction.

5. The method for preparing fluorinated nanoparticles according to claim 1, characterized in that: The volume ratio of tetraethyl orthosilicate to ethanol is (1-5):(50-100); Preferably, the volume ratio of tetraethyl orthosilicate to aminosilane is (2-6):(0.1-4).

6. The method for preparing fluorinated nanoparticles according to claim 1, characterized in that: The aminosilane is a silane coupling agent containing an amino group, preferably at least one of γ-aminopropyltriethoxysilane and γ-aminoethylaminopropyltrimethoxysilane; Preferably, the fluorine-containing ester is an acrylic fluorine-containing ester, and more preferably at least one of trifluoroethyl methacrylate, hexafluoroethyl methacrylate, nonafluoroethyl methacrylate, dodecafluoroethyl methacrylate, trifluoroethyl acrylate, hexafluoroethyl acrylate, nonafluoroethyl acrylate, and dodecafluoroethyl acrylate.

7. Fluorinated nanoparticles prepared by the method according to any one of claims 1 to 6.

8. Use of the fluorinated nanoparticles prepared by the method according to any one of claims 1 to 6 in the preparation of waterproof synthetic leather; Preferably, the synthetic leather is microfiber leather.

9. A method for preparing waterproof synthetic leather loaded with fluorinated nanoparticles, comprising using the fluorinated nanoparticles prepared by the method according to any one of claims 1 to 6, comprising the following steps: The microfiber leather is placed in a fluorinated nanoparticle solution for an in-situ loading reaction, and after the reaction is completed, a waterproof synthetic leather loaded with fluorinated nanoparticles is obtained.

10. The waterproof synthetic leather loaded with fluorinated nanoparticles prepared by the method according to claim 9; Preferably, the surface hydrophobic angle of the waterproof synthetic leather is 151°-159°.